PENGARUH BIMBINGAN PARENTING TERHADAP PENINGKATAN KEMAMPUAN ORANG TUA DALAM MEMBIMBING TUGAS PERKEMBANGAN MORAL DAN NILAI KEAGAMAAN: STUDI TIGA PERSPEKTIF KASUS DI BANDUNG, INDONESIA - Indriyanti; Sugandi Miharja; Bahrudin (Hisbah: Jurnal Bimbingan Konseling dan Dakwah Islam, 2024)
Parenting guidance is a crucial concern for parents as they play a significant role in fostering their children’s moral and religious development, which in turn contributes to their academic success. However, numerous cases indicate a lack of parental involvement in cultivating their children's upbringing, leading to deficiencies in parenting skills. This study aims to enhance the understanding of parenting skills in guiding children towards the development of moral and religious values. Employing a multiple-case study approach, data from TK IT Little Moslem, TK Labschool UPI, and RA Syifaaush Shuduur in Bandung, West Java, Indonesia, were analyzed. Through a quantitative method involving 101 respondents, the study reveals that parenting guidance significantly influences the development of moral and religious values by approximately 61%, while other factors contribute to around 39% of the impact. The findings underscore the pivotal role of parental guidance in enhancing children's learning abilities and fostering an early understanding of morality and religious values. As a result, this research contributes to the existing literature by exploring the nexus between ethics and religions, particularly in the context of parental and teacher guidance in nurturing children during their formative years.   Keywords: Parenting Guidance, Guiding Ability and Moral Religious Values.